The practice of giving in Islam and Buddhism: its impact on man’s spiritual well-being - Ahmad, Masitoh (IIUM Press, 2022)
This paper attempts to explore the significance of almsgiving practice and its impact on man‘s spiritual well-being in the teaching of Islam and Buddhism. It also aims at highlighting the commonalities shared by the two religions in the practice of Giving. It discusses the concept, the purpose, the classification, and the distribution of almsgiving in Islam and Buddhism. The discussion also touches on how almsgiving practices in both religions contribute to the wellbeing of man‘s spiritual life. The study uses qualitative methods in which library research, analytical and comparative methods are applied. The finding shows that both Islam and Buddhism have common ground on the practice of giving, in which both Ṣadaqah and Dāna are mainly practiced to cleanse and purify the inner self from negative qualities and habit such as egoism, self-centrism and to foster compassionate disposition and kindness towards others. The study concludes that the practice of giving is one of the principles which are accepted as one of the most basic human virtues. It plays a vital role in both religions; Islam and Buddhism, and it is always listed as one of the practices in the development of spiritual aspect and sustainability of man‘s spiritual well-being.